The Effect of Crossfit Training on Increasing The Strength Endurance of Middle Distance Athletics Athletes - Moh Gerry Paturohman; Dede Rohmat Nurjaya; Nida'ul Hidayah; Mulyana (Universitas Negeri Semarang, 2025)
Introduction: Strength endurance is an important role in supporting the performance of middle-distance athletic athletes, which can be improved through CrossFit training. Objectives: This study aims to determine the effect of CrossFit training on increasing the strength endurance of middle-distance athletic athletes. Research method: This study uses experimental methods with a quantitative approach, the design used is pre-test post-test control group design. The sample consisted of 20 members of UPI athletic student activity units. Data was collected using an assessment sheet and analyzed using Test Of Homogeneity and Independent T-test. Results and Discussion: The results showed that there were significant differences before and after training in the experimental post-test and control post-test groups with a significant value (2-tailed) of 0.030 (<0.05) or H0 was rejected, which means that CrossFit training has a significant effect on strength endurance. Conclusion: training using CrossFit training is one solution to increase muscle strength endurance in middle-distance athletic athletes.